ANALISIS ZAKAT PRODUKTIF DAN DAMPAKNYA TERHADAP PERTUMBUHAN USAHA MIKRO DAN PENYERAPAN TENAGA KERJA SERTA KESEJAHTERAAN MUSTAHIK DI KOTA PEKANBARU PROVINSI RIAU - Rachmawati, Eka Nuraini; Azmansyah, Azmansyah; Utami, Titis Triatri (Jurnal Ilmu Manajemen, 2019)
This research was conducted on mustahik who received productive zakat from the National Amil Zakat Agency (BAZNAS) in Pekanbaru City. The purpose of this study was to see the effect of productive zakat channeled on increasing mustahik business and increasing welfare. 52 mustahik chosen in this study were conducted using purposive sampling, namely the mustahik of recipients of productive zakat. The analysis was carried out by the bineary logistic regression method because of the welfare variables and business improvement variables in the form of dummy, where the determination of mustahik welfare using the CIBEST method. The results of this study indicate that productive zakat that is distributed does not significantly influence the increase in business and also the welfare of mustahik. this is because the amount of productive zakat distributed does not meet the feasibility of business development, besides that it is still not maximized monetizing and assistance carried out by BAZNAS in the development of mustahik businesses.